Value based management in small and medium enterprises: Analysis of internal and external impulses and possibilities of implementation - Florian Krol (Westfälische Wilhelms-Universität Münster, Lehrstuhl für Betriebswirtschaftslehre, insb. Controlling, 2007)
Since the beginning of the 1990s the shareholder value concept is discussed intensively as being a management concept especially for listed enterprises. In contrast to the immense relevance of small and medium enterprises (SME) for the German economy, value orientation of the management of SMEs is hardly discussed in the literature. In our paper we analyse whether value based management (VBM) and value based management accounting is of importance for SMEs which typically do not have access to the capital market. Based on a detailed literature analysis in a first step we examine internal (such as personal liability of the entrepreneur and the successor problem) and external impulses (e.g. Rating and Basel II) for the implementation of VBM in SMEs. In a second step we analyse the possibilities of implementing VBM in small and medium enterprises. By identifying important value and risk drivers, we show that the specifics of SMEs necessitate a stakeholder value orientation more than a sole shareholder value orientation. This is due to the high interaction of SMEs with their environment. In addition to the capital orientation, social aspects have to be considered in a value based management of SMEs as well. Based on our findings we derive criteria to evaluate the adequacy of management accounting instruments to pursue value orientation in SMEs.
Keywords: 650